HILLARY CLINTON’S POLICIES AND REFORMS (International Educators Conference, 2025)
This paper examines the political strategies and reforms initiated by Hillary Clinton throughout her career. As a prominent figure in American politics, Clinton advocated for healthcare reform, gender equality, and educational advancement. Her diplomatic approach in foreign affairs and efforts to build global partnerships reflect her commitment to stability and human rights. The study highlights her influence on shaping both domestic and international policy.